Anarchism and knowledge: practice, permanence and timeliness - Santos, Luciana Eliza dos (2022)
This text deals with anarchist schooling principles and practices present in movements dealing with education in working-class, popular and free-thinking milieux diffused in urban and rural social contexts of contemporary societies. These schools came to be through political, cultural and social convergences, which left a significant imprint of educational practices that have questioned the different forms of school establishments throughout their history. Thus, a few emblematic anarchist educational practices stand out, as well as their meaning in the History of Education.